2020
DOI: 10.21203/rs.3.rs-117252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Households' Willingness to Pay for Improved Solid Waste Management Services in Gondar city, Ethiopia: Evidence from a double-bounded Dichotomous Contingent Valuation Method

Abstract: Background: Waste is a byproduct of human life. Nowadays, municipal solid waste is being produced in excessive amounts and in this way, both developing and developed countries are facing challenges regarding generation of waste. Economic development, urbanization and improved living standards in cities have contributed to increase in the amount and complexity of solid waste produced. Methods: this study aims to Analysis of households' willingness to pay for improved solid waste management Services in Gondar ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…This study found that 86.3% of the study participants were willing to pay for improving solid waste management services. This is comparable with that of the study conducted in Macau, 85.4% [30]; Gondar, Ethiopia, 87.3% [32]; Bahir Dar, Ethiopia, 86.3% [24]; Injibara town, Ethiopia, 81.06% [25]; and Jimma town, Ethiopia, 83.5% [2]. However, this finding is higher than the study finding in Nepal, 61% [18]; Uganda, 48.1% [22]; and Tanzania, 63% [28].…”
Section: Discussionsupporting
confidence: 89%
“…This study found that 86.3% of the study participants were willing to pay for improving solid waste management services. This is comparable with that of the study conducted in Macau, 85.4% [30]; Gondar, Ethiopia, 87.3% [32]; Bahir Dar, Ethiopia, 86.3% [24]; Injibara town, Ethiopia, 81.06% [25]; and Jimma town, Ethiopia, 83.5% [2]. However, this finding is higher than the study finding in Nepal, 61% [18]; Uganda, 48.1% [22]; and Tanzania, 63% [28].…”
Section: Discussionsupporting
confidence: 89%
“…Some research gets that respondents are willing to increase the fee to improve the solid waste facilities [5] [6] JESSD 2021 IOP Conf. Series: Earth and Environmental Science 940 (2021) 012049 IOP Publishing doi:10.1088/1755-1315/940/1/012049 4 [7]. In Gondar city, Ethiopia, resident WTP is 34.48 and 17.0756 ETB [7].…”
Section: Discussionmentioning
confidence: 99%
“…Series: Earth and Environmental Science 940 (2021) 012049 IOP Publishing doi:10.1088/1755-1315/940/1/012049 4 [7]. In Gondar city, Ethiopia, resident WTP is 34.48 and 17.0756 ETB [7]. In small municipality with no solid waste facility, different waste collection management shcemes pay households WTP between USD 020 to USD 0.75 per month [8].…”
Section: Discussionmentioning
confidence: 99%
“…If the answer was no, then a lower second bid was presented. According to Entele 45 and Wegedie et al, 46 this method produces 4 possible outcomes ( Table 2 ):…”
Section: Methodsmentioning
confidence: 99%